Transformation-deficient mutants of piliated Neisseria gonorrhoeae. - Biswas, G D (1989)
Seven transformation-deficient mutants of piliated, competent Neisseria gonorrhoeae were isolated by screening them for their inability to be transformed by chromosomal DNA after chemical mutagenesis. Three distinct classes of mutants were obtained, each of which was piliated, as determined by electron microscopy. One class exhibited abnormal colony morphology and was unable to take up DNA into a DNase-resistant state. A second class was morphologically normal and took up DNA into a DNase-resistant state normally, but was deficient in both chromosomal and plasmid transformation; mutations in these mutants may affect entry of DNA into the cell proper. A third class was similar to the second but was fully competent for plasmid transformation, suggesting that there was a defect in a late stage of chromosomal transformation.